The Effectiveness of Audio-Visual Educational Media on Premenopausal Women's Knowledge - Wopairi, Paskalina (Jurusan Kebidanan Poltekkes Kemenkes Sorong, 2025)
Health education using audio-visual media can increase premenopausal women's knowledge and participation about the signs and symptoms of premenopause and how to deal with them. The aim of this research is to determine the effectiveness of audio-visual educational media in increasing knowledge about menopause at the Nikiwar Community Health Center. The type of research is quasi experimental research, namely research that tests interventions on a group of subjects, with a research design using a one group pre test-post test design. The sample in this study was women over 40 years of age who showed or had experienced symptoms of menopause and the intervention given was video media about menopause for 7 days. The statistical test used was the Wilcoxon test. The research results showed that the average value of respondents' knowledge increased after being given video media intervention and based on the results of statistical tests it was found that the p-value of respondents' knowledge before and after treatment was 0.00. The conclusion is that there is audiovisual educational media that is effective in increasing mothers' knowledge before and after being given audiovisual media at the Nikiwar Community Health Center.